Knowledge interface co-design of a diabetes and metabolic syndrome initiative with and for Aboriginal people living on Ngarrindjeri country - D. Cameron; A. Wilson; A.E. Mendham; S. Wingard; R. Kropinyeri; T. Scriven; C. Kerrigan; B. Spaeth; S. Stranks; B. Kaambwa; S. Ullah; P. Worley; et al. (Elsevier, 2024)
Objectives: This research program involves two phases to identify enablers and barriers to diabetes care for Aboriginal people on Ngarrindjeri country; and co-design a strength-based metabolic syndrome and Type 2 Diabetes (T2D) remission program with the Ngarrindjeri community. Study design: A study protocol on qualitative research. Methods: The study will recruit Aboriginal people living on Ngarrindjeri country above 18 years of age with a diagnosis of metabolic syndrome or T2D. Recruitment for phases one and two will occur through the Aboriginal Health Team at the Riverland Mallee Coorong Local Health Network. The lived experiences of T2D will be explored with 10-15 Aboriginal participants, through an Aboriginal conversational technique called 'yarning' (60-90 min) in phase 1. Elders and senior community representatives (n = 20-30) will participate in four co-design workshops (2-4 h) in phase 2. Qualitative data will be transcribed and thematically analysed (NVivo version 12). The analysis will focus on protective factors for the Cultural Determinants of Health. Ethics approval was obtained from Aboriginal Health Research Ethics Committee in South Australia (04-22-1009), and Flinders University Human Research Ethics Committee (5847). Results: This work will be used to pilot the co-designed diabetes remission trial. Outcomes will be published in peer-reviewed journals, presented at conferences, focusing on following best practice guidelines from the Australian Institute of Aboriginal and Torres Strait Islander Studies and National Health and Medical Research Council. Research translation will occur through digital posters, manuals, and infographics. Conclusions: The findings will be summarised to all Aboriginal organisations involved in this study, along with peak bodies, stakeholders, Aboriginal Services, and interested participants.